Designing of Project Management Information System for Web-Based OSIS Saturday Clean-Up Attendance Data - Tasya Syalsabilla; Yahfizham Yahfizham (LP2M Universitas Widyatama, 2023)
The rapid progression of technology in today's globalized era has created a heightened demand for efficiency and effectiveness in various aspects of life. This demand is particularly evident in the management of student activities, such as the OSIS clean-up events held on Saturdays. These events, while important for fostering a sense of community and responsibility among students, often face challenges due to manual and non-systematic data management processes. We developed a project management information system to manage attendance and data related to Clean Saturday activities, addressing these challenges. This system utilizes the waterfall method, a structured approach that allows for quickly identifying and resolving issues that may arise during the management process. By implementing this system, Clean Saturday activity management becomes more streamlined and efficient, resulting in improved overall effectiveness. The outcomes of this research are twofold. Firstly, it simplifies the data processing involved in managing attendance at Clean Saturday events, making it easier for OSIS personnel to track and analyze participation. Secondly, it enhances the overall efficiency of the OSIS clean-up program, allowing for better resource allocation and improved outcomes for both students and the community at large.